The contingency effects of environmental uncertainty on the relationship between supply chain integration and operational performance - Wong, Chee Yew; Boon‐itt, Sakun; Wong, Christina W.Y. (Journal of Operations Management, 2011)
AbstractThis paper extends prior supply chain research by building and empirically testing a theoretical model of the contingency effects of environmental uncertainty (EU) on the relationships between three dimensions of supply chain integration and four dimensions of operational performance. Based on the contingency and organizational information processing theories, we argue that under a high EU, the associations between supplier/customer integration, and delivery and flexibility performance, and those between internal integration, and product quality and production cost, will be strengthened. These theoretical propositions are largely confirmed by multi‐group and structural path analyses of survey responses collected from 151 of Thailand's automotive manufacturing plants. This paper contributes to operations management contingency research and provides theory‐driven and empirically proven explanations for managers to differentiate the effects of internal and external integration efforts under different environmental conditions.